Gain characteristic of dilute nitride HELLISH‐VCSOA for 1.3 µm wavelength operation. Issue 4 (22nd January 2013) - Chaqmaqche, F. A. I.; Mazzucato, S.; Balkan, N.; Hugues, M.; Hopkinson, M.
Abstract Optical amplification of more than 3 dB is demonstrated using the Hot Electron Light Emitting and Lasing Semiconductor Heterostructure device in a Vertical Cavity Semiconductor Optical Amplifier configuration (HELLISH‐VCSOA). The device consists of dilute nitride quantum wells Ga0.35In0.65N0.02As0.08/GaAs multiple quantum well (MQW) layers placed in the active region between the doped GaAs claddings and undoped GaAs/AlAs DBRs. Compared to standard VCSOAs in the HELLISH device, the current here does not flow across the distributed Bragg reflectors (DBR) but is injected longitudinally into the p‐ and n‐doped cladding layers. Therefore DBR layers can be undoped, and heating problems en countered in conventional VCSOAs can be avoided. Current‐voltage and spectral characteristics are measured at room temperature under different optical and electrical excitation conditions to demonstrate the possibility of employing this device for amplification purposes (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)